Pharmacological and Toxicological Studies of Essential Oil of Lavandula stoechas subsp. luisieri - Arantes, Sílvia; Candeias, Fátima; Lopes, Orlando; Lima, Mónica; Pereira, Marízia; Tinoco, Teresa; Cruz-Morais, J.; Martins, M. Rosário (Planta Medica, 2016)
The present study was carried out to evaluate the chemical and pharmacological properties of the essential oil of Lavandula stoechas subsp. luisieri, which is a spontaneous shrub widespread in Alentejo (Portugal). Oxygenated monoterpenes, such as 1,8-cineole, lavandulol, and necrodane derivatives, are the main components of essential oil. It revealed important antioxidant activity with a high ability to inhibit lipid peroxidation and showed an outstanding effect against a wide spectrum of microorganisms, such as gram-positive and gram-negative bacteria and pathogenic yeasts. The analgesic effect studied in rats was dose dependent, reaching a maximum of 67 % at 60 min with the dose of 200 mg/kg and the anti-inflammatory activity with this dose caused an inhibition in carrageenan-induced rat paw oedema (83 %) that is higher than dexamethasone 1 mg/Kg (69 %). Besides, animals exhibited normal behaviour after essential oil administration, revealing low toxicity. The essential oil of L. luisieri from Alentejo presents important pharmacological properties and low toxicity, and is a promised candidate to be used as a food supplement or in pharmaceutical applications.
Keywords: Lavandula stoechas subsp. luisieri; Lamiaceae; essential oils; antioxidant; antimicrobial; analgesic; anti-inflammatory